Desain Perkuatan Lereng Pada Tanah Soft Soil Di Ruas Jalan Pakkat – Tara Bintang, Kabupaten Humbang Hasundutan (Km SBG 173 + 000) - Debataraja, Semangat Marudut Tua; Tafonao, Temaziso; Tafonao, Darman (Jurnal Sains dan Teknologi ISTP, 2024)
The Pakkat - Tara Bintang route in Humbang Hasundutan, especially at Km SBG 173+000, often experiences repeated landslides. This area has soil that is easily eroded, especially when it rains. In addition, steep topography with high slopes increases the risk of landslides. The pre-existing DPT cannot effectively withstand the pushing forces of the ground so it is often damaged, causing economic losses and disruption of community access. This research aims to design a more efficient solution for strengthening slopes using reinforced concrete retaining walls. The hope of this design is that it can increase slope stability, reduce the possibility of landslides, and improve accessibility to the Pakkat - Tara Bintang area. The technique used in this research is geotechnical analysis to understand the nature of the soft soil in the area, and calculate the strengthening structures made to withstand lateral pressure from the soil. It is hoped that the resulting design will last longer and provide more effective protection against potential landslides in the future. In other words, the use of reinforced concrete retaining walls to strengthen slopes can greatly increase the resilience of slopes on soft soil, while supporting smooth traffic and improving infrastructure safety in the area.